Spatial and temporal population dynamics of Aspergillus flavus in commercial pistachio orchards in Arizona - Ching’anda, C.; Atehnkeng, J.; Bandyopadhyay, R.; Callicott, K.; Orbach, Michael J.; Cotty, P.J.; Mehl, H.L. (Scientific Societies, 2022)
Aspergillus flavus infects a wide range of crops, including pistachio, and subsequent aflatoxin contamination results in significant economic losses. Application of biocontrol products based on nonaflatoxigenic (atoxigenic) strains of A. flavus is one of the most effective tactics for controlling aflatoxins in crops. Both risk of aflatoxin contamination and effectiveness of biocontrol are influenced by the extent to which A. flavus spores move into pistachio tree canopies during periods of nut development. Thus, the purpose of this study was to evaluate spatial and temporal population dynamics of A. flavus, including the applied biocontrol strain AF36, in canopies of pistachio orchards in Arizona. Propagule densities of A. flavus were quantified on leaf samples collected from lower, middle, and upper canopies from spring through harvest in 2018 and 2019. A. flavus propagule densities peaked during periods of high temperature and rainfall in 2018 (up to 600 CFU/g) and 2019 (up to 23 CFU/g), which coincided with nut development and maturation. The applied biocontrol strain AF36 was detected at all canopy heights but overall propagule densities were greater in the upper and middle canopy (mean = 70 CFU/g) compared with the lower canopy (mean = 47 CFU/g). Results suggest that June to August is the period during which A. flavus inoculum increases in Arizona pistachio orchards and, to most effectively displace aflatoxin-producing fungi in tree canopies, biocontrol applications should precede this period. In addition, this study demonstrates that soil-applied biocontrol strains can successfully disperse throughout the canopies of commercial tree nut orchards.